Numerical evaluations of strain field modification induced by production flaws in loaded composite structures - Raška Jan (EDP Sciences, 2021)
Structural health monitoring (SHM) involves observation and analysis of a system over time using periodically sampled response measurements to monitor the initiation and propagation of a flaw. The article is focused on finite element (FE) modelling of strain field modification induced by flaws in loaded composite structures. Shape of the current production flaw – delamination – was idealised as square with a side of 1 inch. One flaw per laminate in several positions in the layup was considered. The pristine structure was modelled with one element per thickness. For delaminated zone in the centre, the twin coincident elements per thickness were adopted: first element to simulate the lay-up from bottom to delamination, second from delamination to top. The loads and the boundary conditions of the FE model were issued from the tests, based on the ASTM standards: tension test – ASTM D3039, compression after impact test – ASTM D7137 and 4-point bending test – ASTM D7264. Generally, the strain modification is stronger for the delamination near the surface than for the delamination deep in the structure.